2019
DOI: 10.1002/adsc.201801413
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light‐Mediated Synthesis of Enantiopure γ‐Cyclobutane Amino and 3‐(Aminomethyl)‐5‐phenylpentanoic Acids

Abstract: A visible light-mediated [2 + 2] photocycloaddition of amide-linked dienes using [Ir(dtbbpy)(dF(CF 3 )ppy) 2 ]PF 6 as triplet sensitizer was applied to generate a variety of N-tert-butyl, Nbenzyl-and N-tert-butoxycarbonyl-protected 3-azabicyclo[3.2.0]heptan-2-ones in good yields and with good diastereoselectivity. Density functional theory calculations shed light on the conformational prerequisites for the [2 + 2] photocycloaddition. The bicyclic key structures could be readily transformed into g-cyclobutane a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…It was shown that dienes 101 undergo the cycloaddition upon UV irradiation with λ max = 366 nm, which provided the possibility for performing the reaction in common glassware. [460] Furthermore, such transformations could be promoted by visible light using flavin- [461] or iridium-based [462][463][464] photosensitizers. An alternative version of this approach was based on the intramolecular [2 + 2] cycloaddition of allenes; it could be performed in an enantioselective version.…”
Section: Azabicyclo[320]heptanesmentioning
confidence: 99%
“…It was shown that dienes 101 undergo the cycloaddition upon UV irradiation with λ max = 366 nm, which provided the possibility for performing the reaction in common glassware. [460] Furthermore, such transformations could be promoted by visible light using flavin- [461] or iridium-based [462][463][464] photosensitizers. An alternative version of this approach was based on the intramolecular [2 + 2] cycloaddition of allenes; it could be performed in an enantioselective version.…”
Section: Azabicyclo[320]heptanesmentioning
confidence: 99%
“…Serendipitously and somewhat surprisingly, it was found that treatment of 7e with LiOH led to the selective and quantitative removal of a Boc-group rather than ring opening to provide tetracycle 7g , which could not be accessed directly from the [2 + 2] cycloaddition. Indeed, attempts at ring opening the pyrrolidinone of both 7c and 7e to their corresponding γ-amino acids under both basic and acidic conditions were unsuccessful . These tetracycles ( 7c and 7e ) showed remarkable chemical stability and no ring opening was observed under a range of reaction conditions at 100 °C.…”
Section: Derivatization Of Scaffoldsmentioning
confidence: 99%
“…Based on our findings and on previous studies by Reiser and Kwon, [16, 18] the mechanistic considerations for the reaction are shown below in Scheme 4. We also considered a strong dependence between the reaction outcome and conformation adopted by the aryl‐cinnamide, since the rotational barriers around the amide (15–20 kcal mol −1 ) and the ( ortho ‐substituted) Ar‐N (∼20–30 kcal mol −1 ) bonds need to be overcome to achieve a conformation, in which the olefin moieties are close enough to react (Scheme 4, centre) [23] .…”
Section: Resultsmentioning
confidence: 66%